2012
DOI: 10.1155/2012/420156
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Host Metabolic Factors on Treatment Outcome in Chronic Hepatitis C

Abstract: Background. Recent data suggest that chronic hepatitis C has to be considered a metabolic disease further to a viral infection. The aim of this study was to elaborate on the complex interactions between hepatitis C virus, host metabolic factors, and treatment response. Methods. Demographic, virological, and histological data from 356 consecutive patients were analyzed retrospectively. Hepatic steatosis, obesity, and insulin resistance were examined in relation to their impact on treatment outcome. Comparison b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…In our study, the treatment success in the patients with hepatic steatosis was achieved in 62.79% of the patients, whereas in the patients without liver steatosis SVR was achieved in 81.25% of the patients, with statistically significant difference. Similar results were obtained Savvoula et al 17 , in patients with chronic hepatitis C and steatosis treatment success of 56.6% vs 76.8% in the patients without steatosis Werling et al 33 applying the same methodology as in our study, also showed that hepatic steatosis has a negative impact on the effectiveness of antiviral therapy, e. g. 36% of patients with steatosis compared to 71% in patients without steatosis. In their study, not all patients were naive, and all had genotype 1 HCV, and this is the reason for the success of the treatment to be worse than in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the treatment success in the patients with hepatic steatosis was achieved in 62.79% of the patients, whereas in the patients without liver steatosis SVR was achieved in 81.25% of the patients, with statistically significant difference. Similar results were obtained Savvoula et al 17 , in patients with chronic hepatitis C and steatosis treatment success of 56.6% vs 76.8% in the patients without steatosis Werling et al 33 applying the same methodology as in our study, also showed that hepatic steatosis has a negative impact on the effectiveness of antiviral therapy, e. g. 36% of patients with steatosis compared to 71% in patients without steatosis. In their study, not all patients were naive, and all had genotype 1 HCV, and this is the reason for the success of the treatment to be worse than in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the prevalence of liver steatosis in the patients with chronic HCV infection was 34.96%. A similar prevalence of steatosis in patients with hepatitis C by 31.92% found Savooula et al 17 ). Fierbinteanu-Bratićevici et al 18 , found the prevalence of steatosis as 57%, but they applied lower histopathological criteria for the diagnosis of steatosis (≥ 1% of hepatocytes affected by fatty change) and they did not exclude patients with excessive alcohol consumption, which contributed to the greater prevalence of steatosis.…”
Section: Discussionsupporting
confidence: 70%
“…The resulting prevalence of steatosis was lower compared with the data of most authors, due to heterogeneous criteria, different demographic characteristics of the sample and different share of genotype 3 HCV. The closest prevalence of steatosis was obtained in the research of Greek authors (31.74%) and the research of Pakistani authors (39%) where there was a group of patients with very similar demographic and clinical characteristics and the same histological criteria for the diagnosis of steatosis 31,32 . An interesting research was conducted by Pais et al 33 instead of liver biopsy and found that 43% of respondents with CHC had signs of steatosis, which was also similar to our result.…”
Section: Discussionmentioning
confidence: 66%